Produtividade e absorção de nutrientes de três cultivares de batata-doce [Ipomoea batatas (L.) Lam] selecionadas para a produção de etanol - Gonçalves, Rogério Cavalcante (Universidade Federal do Tocantins, 2020)
The growing demand for energy has pushed the development of more efficient systems and technologies and diversification of supply sources, especially renewable and clean energy. Brazil is considered one of the countries that have the best conditions for sustainable production of ethanol and the potential of being the largest producer. Thus, in addition to sugar cane which already represents 18.2% of primary energy sources in Brazil, other crops that can contribute to the diversification of the energy matrix of the country need to be studied. Among the starchy crops, sweet potato has been the subject of research for more than a decade by researchers at the Federal University of Tocantins (UFT). The result of these studies, if structured a breeding program aimed to increase the biomass of sweet potato, for the production of ethanol. These studies resulted in of cultivars with yields between 32 and 65 t ha-1 under the conditions of the State of Tocantins and increases of 10% to 15% in starch. It is noteworthy that the planting of cultivars with high productivity does not guarantee the optimization of ethanol production, as well as its sustainability, where a major challenge is the need to know the nutritional requirement related to absorption efficiency and fertilizer management. This work included conducting an experiment at the Experimental Station of the Federal University of Tocantins, UFT, Palmas, where the cultivars of sweet potato Marcela, Amanda and Duda, obtained from the breeding program of the UFT, were evaluated according of different doses of N, P2O5 and K2O applied to the soil. The experiment comprised 33 treatments arranged in a randomized block design with four replications. At 90 days of culture samples were taken from leaves and soil for characterization of foliar N, P and K and the availability of nutrients in the soil. At the end of the crop cycle cultivars, shoots and roots of the plants were harvested for characterization of biomass (leaves and stems) of shoot, root yield and starch content. Foliar N, P and K, obtained after 90 days of culture, showed no significant differences among cultivars. Comparing the yield obtained with the control treatment (without NPK fertilization, soil with 5 mg dm-3 of P, 145 mg dm-3) among the three cultivars, the highest yield was obtained with Duda followed by Amanda and Marcela. Moreover, when considering the average yield obtained from each cultivar due to different doses of nutrients Marcela showed the greatest response to fertilization, with 95 % productivity increase (from 14 t ha-1 to 27, 3 t ha-1) followed by Amanda with 52 % (13.6 t ha-1 to 22.6 t ha-1) and Duda with 28% (33.0 t ha-1 to 47.0 t ha- 1). The greater efficiency of nitrogen fertilization (324 kg kg-1) was obtained with a dose of 240 kg ha-1 with Amanda, while phosphorus (207 kg kg-1) and potassium (224 kg kg-1) with the dose of 300 kg ha-1 with the cultivar Duda. Productivity and starch content in the storage roots varied depending on the cultivar and nitrogen, phosphorus and potassium applied to the soil. Cultivar Duda accumulated more nutrients in the leaves, but that was the least accumulated nutrients in the stems and roots than the other cultivars, however, showed the highest average productivity. On the other hand, the cultivar Amanda had the highest exports of nutrients in their stems and roots. The increase of biomass of roots resulted in the tendency of decrease in starch concentration, indicating a dilution effect. The recommended doses of N and P2O5 for Amanda cultivar were higher than those recommended for other cultivars, whereas the highest dose of K2O was recommended to cultivate Duda.